A Hybrid Fluid-Solid Interaction Scheme Combining the Multi-Component Diffuse Interface Method and the Material Point Method (Communications in Computational Physics, 2023)
We propose a hybrid scheme combing the diffuse interface method and thematerial point method to simulate the complex interactions between the multiphasecompressible flow and elastoplastic solid. The multiphase flow is modelled by themulti-component model and solved using a generalized Godunov method in the Eulerian grids, while the elastoplastic solid is solved by the classical material point methodin a combination of Lagrangian particles and Eulerian background grids. In order to facilitate the simulation of fluid-solid interactions, the solid variables are further interpolated to the cell center and coexist with the fluid in the same cell. An instantaneous relaxation procedure of velocity and pressure is adopted to simulate the momentum andenergy transfers between various materials, and to keep the system within a tightlycoupled interaction. Several numerical examples, including shock tube problem, gas-bubble problem, air blast, underwater explosion and high speed impact applicationsare presented to validate the numerical scheme.
Keywords: Multiphase flow; elastoplastic solid; diffuse interface method; material point method; fluid-solid interaction.